Soviet prosecutor about activity of repressive structures and resistance movement in Lithuania in post war. - Starkauskas, Juozas (Genocidas ir rezistencija, 2003)
This publication contains two summary reports drafted by the military prosecutor of the Lithuanian border district of the MVD army, addressed to Antanas Sniečkus, the Central Committee of the Lithuanian Communist Party (LKP(b)), and one, apparently presented at a meeting of Chekist commanders. All of them reveal a broad panorama of operations of the repressive structures of the occupying regime in Lithuania.